Early Industrialization and Inequality in Toronto, 1861-1899 - Darroch, A. Gordon (Labour / Le Travail, 1983)
Using samples of available assessment roll data for Toronto, this article maps patterns of inequality, by decades, over the years of early industrialization, 1861 -1899. The limits of these data and the many legal exclusions are reviewed; it is argued that assessed values best represent differences in everyday living conditions, rather than in wealth, property or income. Several ways of examining the extent of inequality are considered. As expected, inequality among households was pronounced, although several measures revealed an intriguing pattern of initial increase in inequality, 1861-1871, and subsequent, modest decline to the end of the century. An attempt to account for the pattern in terms of the aging of the city population turned up only very limited effects. Some implications of the patterns are considered for the analysis of class and household economies.